2022
DOI: 10.3390/nu14193958
|View full text |Cite
|
Sign up to set email alerts
|

Realgar Alleviated Neuroinflammation Induced by High Protein and High Calorie Diet in Rats via the Microbiota-Gut-Brain Axis

Abstract: Purpose: Gastrointestinal heat retention syndrome (GHRS) often occurs in adolescents, resulting into nervous system injury. Realgar, an arsenic mineral with neuroprotective effect, has been widely used to treat GHRS. However, its mechanism of action remains unknown. Methods: A GHRS rat model was established using a high protein and high calorie diet. We performed macroscopic characterization by assessing bowel sounds, hot/cold preference, anal temperature, and fecal features. Atomic fluorescence spectroscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[24] However, excessive amounts of realgar can have toxic effects on the central nervous system of normal rats. [25]…”
Section: Modern Pharmacological Research On Realgarmentioning
confidence: 99%
See 2 more Smart Citations
“…[24] However, excessive amounts of realgar can have toxic effects on the central nervous system of normal rats. [25]…”
Section: Modern Pharmacological Research On Realgarmentioning
confidence: 99%
“…[24] However, excessive amounts of realgar can have toxic effects on the central nervous system of normal rats. [25] 3.3. Antitumor mechanisms Realgar has demonstrated significant clinical efficacy in the treatment of leukemia, particularly APL, with good safety, low toxicity, and fewer adverse effects such as bone marrow suppression.…”
Section: Protective Effects On the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The obesity-related ecological imbalance is directly associated with the high-fat diet (HFD) and manifests in a reduced overall microbiota count, a shift in bacteria species abundance, and an overall increase in gut permeability [20,21]. Also, studies have shown that a high-calorie diet in rats induced decreased bowel sounds and fecal microbial imbalance [22]. The increase in unfavorable bacteria (such as Lachnoclostridium and Desulfovibrio) was strongly associated with a disturbance of glucose and lipid metabolism [23].…”
Section: Introductionmentioning
confidence: 99%